A primary Corynebacterium pseudotuberculosis low dose infection in alpacas (Lama pacos) protects against a lethal challenge exposure - Braga W. (2007)
Especial thanks to Dr. James Higgins for statistical consultation and to Mrs. Jacque Staat and Mrs. Megan Haugh for the manuscript review. This work was supported by the International Foundation of Science IFS Stockholm Sweden, Grant B:2083-2 and the Consejo Nacional de Ciencia y Tecnologia CONCYTEC, Lima, Peru.